2008
DOI: 10.1016/j.scriptamat.2008.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring damage accumulation in ceramic matrix composites using electrical resistivity

Abstract: The electric resistance of woven SiC fiber reinforced SiC matrix composites were measured under tensile loading conditions. The results show that the electrical resistance is closely related to damage and that real-time information about the damage state can be obtained through monitoring of the resistance. Such self-sensing capability provides the possibility of on-board/in-situ damage detection and accurate life prediction for hightemperature ceramic matrix composites.Woven silicon carbide fiber-reinforced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 21 publications
4
46
1
1
Order By: Relevance
“…At that point, the resistance increased linearly (the AE events also resumed). Unlike the CVI material tested previously 23 , the cyclic loading resulted in a higher resistance for each cycle. That is to say, after unloading and then re-loading to the same stress, the resistance was higher than before.…”
Section: Test Procedures and Damage Assessmentmentioning
confidence: 62%
See 1 more Smart Citation
“…At that point, the resistance increased linearly (the AE events also resumed). Unlike the CVI material tested previously 23 , the cyclic loading resulted in a higher resistance for each cycle. That is to say, after unloading and then re-loading to the same stress, the resistance was higher than before.…”
Section: Test Procedures and Damage Assessmentmentioning
confidence: 62%
“…Previous work with chemical vapor infiltrated (CVI) SiC/SiC composites has shown a direct relationship between matrix crack density and resistance change for samples subjected to creep conditions 22 . Room temperature monotonic tensile tests have also been conducted concerning this material 23 . Typically, the resistance changes were on the order of 50% for both test conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The coated and uncoated samples show increases in electrical resistance of 220% and 180% over the entire specimen length, with measured increases in gage-section strain of 0.371% and 0.134% respectively. As is the case of room temperature tensile loading of SiC/SiC composite systems [22][23], the ER increase in these tests appears to be strongly related to damage accumulation. In the case of room temperature tests, the high volume fraction of free bonded composites segments, debonded fiber/matrix regions and matrix cracks bridged solely by the reinforcing fibers [23].…”
Section: Accepted Manuscriptmentioning
confidence: 69%
“…Ideally, such techniques would be simple to implement on a material level as well as a structural testing scale. Recent studies have shown the viability of using in-situ modal acoustic emission (AE) and electrical resistance (ER) monitoring of SiC/SiC CMC specimens during room temperature monotonic tensile loading in order to detect damage onset and accumulation in both CVI[22] and MI-CVI matrices[23]. These works were successful in determining a correlation between electrical resistance increase and stressdependent transverse matrix cracking.…”
mentioning
confidence: 99%
“…Such measurements include those via optical microscopy (108)(109)(110)(111)(112)(113), scanning electron microscopy (114-119), speckle interferometry (120)(121)(122), acoustic waves (123)(124)(125), and electrical resistance (126,127). Most of these measurements were at room temperature; only a few studies tackled in situ measurements at high temperatures (e.g., References 114 and 128).…”
Section: Test Data: the High-temperature Challengementioning
confidence: 99%